The JCVI standard operating procedure for annotating prokaryotic metagenomic shotgun sequencing data. Issue 2 (March 2010) - Tanenbaum, David; Goll, Johannes; Murphy, Sean; Kumar, Prateek; Zafar, Nikhat; Thiagarajan, Mathangi; Madupu, Ramana; Davidsen, Tanja; Kagan, Leonid; Kravitz, Saul; Rusch, Douglas; Yooseph, Shibu
Abstract The JCVI metagenomics analysis pipeline provides for the efficient and consistent annotation of shotgun metagenomics sequencing data for sampling communities of prokaryotic organisms. The process can be equally applied to individual sequence reads from traditional Sanger capillary electrophoresis sequences, newer technologies such as 454 pyrosequencing, or sequence assemblies derived from one or more of these data types. It includes the analysis of both coding and non-coding genes, whether full-length or, as is often the case for shotgun metagenomics, fragmentary. The system is designed to provide the best-supported conservative functional annotation based on a combination of trusted homology-based scientific evidence and computational assertions and an annotation value hierarchy established through extensive manual curation. The functional annotation attributes assigned by this system include gene name, gene symbol, GO terms [1], EC numbers [2], and JCVI functional role categories [3].